A model to assess the feasibility of shifting reaction equilibrium by acetone removal in the transamination of ketones using 2‐propylamine. Issue 2 (26th August 2013) - Tufvesson, Pär; Bach, Christian; Woodley, John M.
ABSTRACT Acetone removal by evaporation has been proposed as a simple and cheap way to shift the equilibrium in the biocatalytic asymmetric synthesis of optically pure chiral amines, when 2‐propylamine is used as the amine donor. However, dependent on the system properties, this may or may not be a suitable strategy. To avoid excessive laboratory work a model was used to assess the process feasibility. The results from the current study show that a simple model of the acetone removal dependence on temperature and sparging gas flowrate can be developed and fits the experimental data well. The model for acetone removal was then coupled to a simple model for biocatalyst kinetics and also for loss of substrate ketone by evaporation. The three models were used to simulate the effects of varying the critical process parameters and reaction equilibrium constants (K eq) as well as different substrate ketone volatilities (Henry's constant). The simulations were used to estimate the substrate losses and also the maximum yield that could be expected. The approach was seen to give a clear indication for which target amines the acetone evaporation strategy would be feasible and for which amines it would not. The study also shows the value of a modeling approach in conceptual process design prior to entering a biocatalyst screening or engineering program to assess the feasibility of a particular process strategy for a given target product. Biotechnol. Bioeng. 2014;111: 309–319. © 2013 Wiley Periodicals, Inc.